PENGARUH PENAMBAHAN SERAT POLYVINYL ALCOHOL DAN SUPERPLASTISIZER POLYCARBOXYLATE ETHERS TERHADAP SIFAT MEKANIK MATERIAL ECC - Sadjuri, Harsisto (Jurnal Metalurgi, 2024)
This research was conducted to study the effect of PVA fiber and polycarboxylate ethers typed superplastisizer (type P) to the mechanical properties of ECC materials. The purpose of the use of PVA is to increase the strength of the concrete so that when subjected to load, type of fracture is microcrack. Superplasticizer was added to enhance ECC workability so it was easily compressed and get better quality. ECC material testing was conducted by measuring the compressive and flexural strength using a universal testing machine. The most effective composition of ECC material on the ratio of cement: water: sand: fly ash: SP: PVA = 1 : 0.68 : 0.94 : 1.6 : 0.01 : 0.02 has compressive and flexural strength of 196 kg/cm2 and 145.3 kgf respectively.